Peran Pemuda Dalam Mewujudkan Pendidikan Karakter Nasionalisme Dengan Mempertahankan Kearifan Lokal - Jati, Dionisius Heckie Puspoko; Listiarum, Febri; Aprilia, Harlis; Oktovian, Alphonsus Ulung Tegar (Jayapangus Press, 2025)
Nationalism is a character trait that reflects attitudes, values, and behaviors demonstrating love, pride, and responsibility towards the nation and the state. Nationalism is not just about love for the homeland, but also includes a commitment to maintaining unity, advocating for common interests, and respecting the diversity present in society. As the next generation, youth bear a significant responsibility in balancing modernization with the preservation of local traditions. This study aims to analyze the role of youth in cultivating the character of nationalism while preserving local wisdom amidst globalization. The research uses a qualitative approach with literature study and in-depth interviews involving youth, community leaders, and cultural practitioners. The focus of the study is on how youth can be a driving force in integrating local wisdom values into daily life without neglecting innovation and progress. The research was conducted in the Tabaggunung Hamlet, Brongkol Village, Jambu Subdistrict, Semarang Regency. This location was chosen because the local culture and wisdom are still thriving. The study began with coordination with the head of Tabaggunung Hamlet, followed by a Focus Group Discussion (FGD). Subsequently, FGDs and in-depth interviews were conducted with several youths, community leaders, and cultural practitioners. The researcher also planned a cultural performance or local cultural attraction presented by the community as a simple demonstration of local culture. This cultural attraction supports the research data regarding the role of youth. The research findings are: (1) Fostering the younger generation in developing and preserving local cultural wisdom, (2) Preserving local cultural wisdom through local arts, (3) Building character education for the community through local arts.